2021
DOI: 10.12659/msm.934463
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Surgical Outcomes in 60 Patients with Crohn Disease from a Single Center in Poland

Abstract: Background In Crohn disease (CD), pharmacotherapy with nutritional support is the treatment of choice. However, complications and a lack of response to drugs are indications for surgery. The aim of this study was to present indications for surgery and methods of surgical treatment of CD and to analyze the postoperative morbidity and mortality risk factors. Material/Methods This was a retrospective analysis of adult patients who underwent surgery for CD between January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 51 publications
1
6
1
Order By: Relevance
“…There are also discussions about the preoperative use of biological treatment and the risk of postoperative complications. Some researchers described the lack of a relationship between increased serum anti-TNF alpha levels and adverse effects after surgery or rehospitalization [27,42,46], which correspond with the results obtained during our analysis and with the observations from a similar study in our clinic [15]. Kunitake et al and Bregnbak et al observed only longer hospitalization time in patients treated with infliximab [46,47], while Schluender et al described significantly more frequent occurrence of postoperative complications during the concomitant use of infliximab and cyclosporin A, with no such effect during treatment only with a biological drug [48].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There are also discussions about the preoperative use of biological treatment and the risk of postoperative complications. Some researchers described the lack of a relationship between increased serum anti-TNF alpha levels and adverse effects after surgery or rehospitalization [27,42,46], which correspond with the results obtained during our analysis and with the observations from a similar study in our clinic [15]. Kunitake et al and Bregnbak et al observed only longer hospitalization time in patients treated with infliximab [46,47], while Schluender et al described significantly more frequent occurrence of postoperative complications during the concomitant use of infliximab and cyclosporin A, with no such effect during treatment only with a biological drug [48].…”
Section: Discussionsupporting
confidence: 91%
“…A similar study that assessed the most common indications for surgery (ie, fistulae and strictures) and the methods (ie, right hemicolectomy) and results of surgical treatment of another principal type of inflammatory bowel disease, Crohn’s disease, in the same department as our referral Department of Digestive Tract Surgery, University Clinical Center, Medical University of Silesia in Katowice, was performed and the results can be compared with those of the present study [ 5 ]. The aim of our research was to determine the most common indications for surgical treatment of ulcerative colitis, along with methods and results of this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is a known risk factor for the development of CD and for worse clinical outcomes among patients who have the disease. Smoking has been associated with increased frequency of disease flares [1][2][3][4], increased need for a firstor second-time surgery [1], and earlier age at which the first surgery was required [5]. Further, several studies have shown that smoking is a risk factor for recurrence of the disease after surgery and for recurrence of fistula [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although all these different factors have similar patterns of association with both CD and UC, smoking has a distinct interaction with these two diseases. In specific, it has been associated with a detrimental effect on the development and course of CD [4, 5] compared to a possible beneficial effect on the progression of UC [4]. In fact, many studies have confirmed these associations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation